Antioxidant status of rats’ blood and liver affected by sodium selenite and selenium nanoparticles - Urbánková, Lenka; Horký, Pavel; Skládanka, Jiří; Přibilová, Magdalena; Smolíková, Vendula; Nevrkla, Pavel; Cernei, Natalia Vladimirovna; Lacková, Zuzana; Hedbávný, Josef; Ridošková, Andrea; Adam, Vojtěch; Kopel, Pavel (PeerJ, 2018)
Background: Selenium is an essential element; however, at higher doses, it can be toxic. Therefore, alternative nanotechnological solutions are required to overcome toxicological issues, rather than conventional alternatives. Nanoparticles show new and promising properties that may be able to suppress toxicity while maintaining the positive effects of selenium on an organism. The aim of the experiment was to determine the influence of sodium selenite and selenium nanoparticles (SeNPs) on the antioxidant status of rats. Methods: The males of the outbreed rat strain Wistar albino were selected as a model organism. Animals were fed different forms of selenium. The control group was given a mixture without selenium addition, whereas other groups were fed a mixture containing sodium selenite, Se-49, and Se-100 SeNPs respectively. The duration of the trial was 30 days. Results: Analysis of blood and liver was performed where the concentration of reduced (GSH) and oxidised (GSSG) glutathione, and total selenium content were measured. In the liver, a significant reduction in GSSG was found for all experiment groups. Blood samples showed a significant reduction in GSH and an increase in GSSG. Discussion: These results show that SeNPs may be an alternative to dietary selenium for animal organisms.

Background: Selenium is an essential element; however, at higher doses, it can be toxic. Therefore, alternative nanotechnological solutions are required to overcome toxicological issues, rather than conventional alternatives. Nanoparticles show new and promising properties that may be able to suppress toxicity while maintaining the positive effects of selenium on an organism. The aim of the experiment was to determine the influence of sodium selenite and selenium nanoparticles (SeNPs) on the antioxidant status of rats. Methods: The males of the outbreed rat strain Wistar albino were selected as a model organism. Animals were fed different forms of selenium. The control group was given a mixture without selenium addition, whereas other groups were fed a mixture containing sodium selenite, Se-49, and Se-100 SeNPs respectively. The duration of the trial was 30 days. Results: Analysis of blood and liver was performed where the concentration of reduced (GSH) and oxidised (GSSG) glutathione, and total selenium content were measured. In the liver, a significant reduction in GSSG was found for all experiment groups. Blood samples showed a significant reduction in GSH and an increase in GSSG. Discussion: These results show that SeNPs may be an alternative to dietary selenium for animal organisms.
Antioxidant status of rats’ blood and liver affected by sodium selenite and selenium nanoparticles
Keywords: Selenium nanoparticles; Glutathione; Rat; Animal nutrition; Antioxidant; Selenium nanoparticles; Glutathione; Rat; Animal nutrition; Antioxidant